Saisonalität von organischem Kohlenstoff im Oberflächenwasser des subpolaren Nordatlantiks - Dunker, Mirja (2013)
Studies of organic carbon cycling in the ocean are of great importance, since dissolved (DOC) and particulate organic carbon (POC) are directly related to the dissolved inorganic carbon (DIC), which is a macronutrient for marine organisms and controls the efficiency of the marine carbon pump by which atmospheric carbondioxide (CO2) is exported to the deep ocean. It is therefore important to understand the seasonality, the different sources and sinks of DOC and POC and its influences on the oceanic processes. The main goal of this work is to determine the seasonality of DOC and POC in the surface waters of the subpolar North Atlantic. The work consists of three main parts: (1) Method Optimization The TOC-VCSN-instrument from Shimadzu, for the determination of total organic carbon (TOC), is put back into operation and the measurement procedure should be optimized. The system is based on the HTCO-method by Sharp [1973], the carbon detection limit is 4 μmol L-1 [Shimadzu, 2001], and about 20 TOC samples may be analyzed within 24 hours with a reproducibility of 2.3 μmol L-1 and an accuracy of 1.5 μmol L-1. In addition to the conversion of the gas lines and the connection of a nitrogen gas bottle for the purge process, self-packed quartz tube halogen scrubber were used (improved visual control capability). A pretreatment procedure of the new, more effective catalyst was developed, which is more rapidly stable at lower blank values. (2) Analysis of samples of the M/V Atlantic Companion cruises The determination of DOC and POC are made from surface seawater samples that were taken on board the M/V Atlantic Companion in the North Atlantic between 10 °W and 55 °W from October 2011 to October 2012. The determined DOC concentrations range from 40 to 111 μmol kg-1, the oncentrations of the POC include a span from 3.4 to 45 μmol kg-1. In addition, the temperature, salinity and nitrate and climatological data of the mixed layer depth and chlorophyll satellite images are used for analysis. The concentrations of DOC are ...